2007
DOI: 10.1007/bf02913333
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidant status in cervical cancer patients

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 9 publications
8
76
0
2
Order By: Relevance
“…On the contrary, a decrease of SOD activity was detected in blood cells of patients with cervical cancer. The decrease of SOD activity observed could be related to the generation of free radicals that cause direct damage to the enzyme by reticulation or mutation induction (Manoharan et al, 2004;Naidu et al, 2007). Besides, this decrease may be caused by an alteration of the oligoelements (essential trace elements) that act as cofactors of this enzyme, which may be considered as a risk factor of tumor growth or carcinogenesis (Naidu et al, 2007).…”
Section: Ros Adaptation By Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, a decrease of SOD activity was detected in blood cells of patients with cervical cancer. The decrease of SOD activity observed could be related to the generation of free radicals that cause direct damage to the enzyme by reticulation or mutation induction (Manoharan et al, 2004;Naidu et al, 2007). Besides, this decrease may be caused by an alteration of the oligoelements (essential trace elements) that act as cofactors of this enzyme, which may be considered as a risk factor of tumor growth or carcinogenesis (Naidu et al, 2007).…”
Section: Ros Adaptation By Cancer Cellsmentioning
confidence: 99%
“…The decrease of SOD activity observed could be related to the generation of free radicals that cause direct damage to the enzyme by reticulation or mutation induction (Manoharan et al, 2004;Naidu et al, 2007). Besides, this decrease may be caused by an alteration of the oligoelements (essential trace elements) that act as cofactors of this enzyme, which may be considered as a risk factor of tumor growth or carcinogenesis (Naidu et al, 2007). On the other hand, it was observed that the increase in the intensity of oxidative stress in the blood of patients with ovarian cancer is accompained by a decrease of antioxidants like SOD, catalase, vitamin C and vitamin E (Senthil et al, 2004).…”
Section: Ros Adaptation By Cancer Cellsmentioning
confidence: 99%
“…24 Advanced cancer patients have deficiency of essential micronutrients like zinc, selenium, vitamin C and vitamin E, which support body's immune response. [25][26][27][28] …”
Section: Consequences Of Malnutritionmentioning
confidence: 99%
“…This protects the cell membrane from damage by ROS. But the decreased SOD levels may lead to increased lipid peroxidation resulting in the cellular rigidity and deformability [6]. This phenomena, i.e.…”
Section: Introductionmentioning
confidence: 99%